Implementation of The Concept of Conservation Area Buffer Zone in Indonesia - Salwa Nadhira; Sambas Basuni (Jurnal Manajemen Hutan Tropika, 2021)
Conservation area buffer zones are recognized to provide ecological, social, and economic benefits in supporting conservation areas' integrity. Nevertheless, little is known hitherto about the development dynamics of conservation area buffer zones in Indonesia. Therefore, a study concerning theory, policy, and management of the conservation area buffer zones in Indonesia is necessary to analyze its performance, identify problems in its implementation, and formulate its evidence-based development policy. This study aims to identify and analyze issues in implementing the concept of conservation area buffer zone as well as recommend policy formulation to accelerate the development of conservation area buffer zones in Indonesia. This study is an exploratory research through a literature review with semi-systematic approach. It finds that there are only nine out of 530 (1.7%) conservation areas in Indonesia with a formally established buffer zone. This condition is mainly due to the absence of buffer zone institutions at the regional government levels. Meanwhile, the management of supposedly buffer zones has been conducted through various projects for strengthening the functions of buffer zones by conservation area managers, either in the form of land-based or non-land-based projects. This study results in recommendations for all interested parties to urge the Ministry of Environment and Forestry and the Ministry of Home Affairs to promulgate and renew the regulations concerning the procedures of establishing and managing conservation area buffer zones. Moreover, regarding the institutional aspect, there is a need for a particular structure in both ministries to address community empowerment issues at the site level.